3D micromorphology evaluation of kefir microbial films loaded with extract of Amazon rainforest fruit Cupuaçu. (March 2021) - Matos, Robert S.; Pinheiro, Bianca S.; Souza, Izabella S.; Paes de Castro, Ruy R.; Ramos, Glenda Q.; Pinto, Erveton P.; Silva, Romualdo S.; da Fonseca Filho, Henrique D.
Highlights: We successfully obtained kefir biofilms prepared with Cupuaçu extract. A complete surface assessment based on the stereometric and fractal behavior of kefir biofilms was provided. Morphology showed a poor growth of microorganisms on the surface at low concentrations and, for highest, a greater abundance. Stereometric and fractal parameters showed the highest concentration had the highest roughness and microtexture homogeneity. Abstract: We performed qualitative and quantitative analysis of surfaces of kefir biofilms loaded with Amazon rainforest fruit extract. Scanning electron microscopy and atomic force microscopy were used to evaluate the micromorphology of the biofilms. The films surface displayed a lower density of microorganisms (∼ 0.061 microorganisms/μm 2 ) for the lowest concentration of fruit extract, however, a greater density (∼0.220 microorganisms/μm 2 ) was observed for the higher concentration. Height stereometric parameters revealed that the biofilms with the highest concentration presented the highest roughness. However, almost all the stereometric parameters related to texture showed no significant difference. Furthermore, the Hurst coefficients of the average power spectrum density were similar for all biofilms. Fractal parameters confirmed that higher concentrations of fruit extract induced a superior topographic irregularity. However, fractal lacunarity does not show any significant difference confirming the similarity of the microtextures. Moreover, fractal succolarity and surface entropy exhibited values that suggested ideal percolation and strong topographic uniformity, respectively, indicating that these films can uniformly adhere to other surfaces. Our results confirm that the stereometric and fractal parameters can be relevant for the surface characterization of microbial films, which can be of great importance to the biomedical field.